Determination of maximal lactate steady state using the talk test - Lueck, Justine M. (My University, 2011)
Because of the relationship between training intensity and blood lactate accumulation, maximal lactate steady state (MLSS) can be a valuable tool to determine appropriate exercise intensity. The Talk Test has also been shown to be a valuable tool for exercise intensity in a variety of populations. This study was done to evaluate whether the Talk Test can be used to define MLSS. Fourteen well trained subjects completed 2 maximal tests to determine the stages for the subsequent tests, which included: the stage the subject was unsure whether speech was comfortable (EQ), the last stage the subject could speak comfortably (LP), and the stage before the LP (LP-l). Following the determination of these speeds, each subject completed 30 minute steady state runs at each of the Talk Test identified intensities with measurement of blood lactate at 0, 10, 20, and 30 minutes to define whether MLSS is related to Talk Test intensity. Significant differences were found in heart rate, RPE, Talk Test score, and blood lactate concentration for Talk Test conditions. Bonferroni corrected T-Tests demonstrated further differences at Talk Test conditions and time values. Changes in blood lactate concentration were <1.0mmol*r1 for each subject at the LP-l condition, and for 12 of the 14 subjects in the LP and EQ conditions. This demonstrated that MLSS was not reached on average by the subjects, even at the EQ Talk Test condition. In this population of highly trained individuals, most subjects were still below the intensity MLSS even when exercising at the EQ Talk Test intensity.
Keywords: Exercise tests.; Exercise - Physiological aspects.; Exercise.